Electric vehicles in Iceland : private consumer market 2013 - 2017 - Tinna Kjartansdóttir 1975- (2012)
The deduction of greenhouse gas emission and less dependence on fossil fuels has led to the introduction of electric vehicles to the global marketplace. Electric cars have gone through turbulent times since their introduction and challenges concerning batteries and charging are still present. The global market is slowly accepting alternative energy sourced vehicles and fully electric cars have already gained a small share of that market. Iceland has recently introduced electric cars and 14 cars have been sold so far. This research focuses on the private consumer market in Iceland, the possibility of growth for the next 5 years and the segments that will be the most ideal for targeting. A market survey was conducted with the main focus on consumer attitude and purchasing behavior and market conditions and product development was researched with a qualitative study. The automotive market in Iceland is slowly recovering from a deep financial crisis and the car dealerships are taking electric car entries with caution or not at all. Currently, there are two versions of the same electric car available in Iceland and in 2013 a few more models are expected to enter the market. The Icelandic government is supporting the alternative fuel vehicle development and has set future targets for lower CO2 emissions. Incentives and tax cuts have been implemented and there are suggestions for further incentive increases. The consumer survey showed that the consumer attitude is positive as the majority of the participants could see themselves buying electric cars in the next five years. The survey also showed that consumer awareness and knowledge about electric cars is low. A projection was made for the 5 year outlook with three different scenarios that included market variables such as government incentives, charging infrastructure and increased dealership effort. The outlook projections assume for a total market share in the range of 0.5%-2%. By using early adopters of innovation theory and segmentation, the ideal target groups ...